Case Report: A Variety of Immune-Related Adverse Events Triggered by Immune Checkpoint Inhibitors in a Subject With Malignant Melanoma: Destructive Thyroiditis, Aseptic Meningitis and Isolated ACTH Deficiency - Katakura, Yukino; Kimura, Tomohiko; Kusano, Takashi; Tatsumi, Fuminori; Iwamoto, Yuichiro; Sanada, Junpei; Fushimi, Yoshiro; Shimoda, Masashi; Kohara, Kenji; Nakanishi, Shuhei; Kaku, Kohei; Mune, Tomoatsu; et al. (Frontiers in Endocrinology, 2021)
Recently, immune checkpoint inhibitors have been drawing much attention as cancer immunotherapy, but it has been shown that various immune-related adverse events are induced by immune checkpoint inhibitors in various organs which becomes one of serious issues at present. A 58-year-old Japanese male with malignant melanoma was treated with nivolumab and/or ipilimumab. During the period of treatment, he suffered from various immune-related adverse events. First, about 1 month after starting nivolumab monotherapy, destructive thyroiditis was induced, and then we started replacement therapy with levothyroxine. Second, about 1 month after starting nivolumab and ipilimumab combination therapy, aseptic meningitis was induced. We stopped both drugs and started steroid therapy with prednisolone. Finally, about 9 months after re-starting nivolumab, isolated ACTH deficiency was induced, and then we started replacement therapy with hydrocortisone. Taken together, we should bear in mind the possibility of a variety of immune-related adverse events when we use immune checkpoint inhibitors.